New-style Banks and The Agent Governance Strategies of the Beiyang Government: A Study on the History of the Development of China's Documentary Railway Billing Business in Modern Times - Kun Zhou, (Tạp chí Khoa học Xã hội và Nhân văn (VNU Journal of Social Sciences and Humanities), 2025)
Under the "weak state" regime of modern China, it was difficult for the country’s modernization process to develop without the effective intervention of a centralized state. In the process of government governance, absorbing social organizations and civil forces as agents had proved to be an effective method. Beiyang government’s governance strategy of ‘using agents to regulate agents’ in the documentary railway billing business could be regarded as typical of the diversity of government management. Qing Dynasty, government departments were not directly responsible for railway freight for various reasons, instead, they allowed railway transshipment companies to act as agents for freight management. Then transshipment companies gradually became an obstacle to Beiyang government’s reform on freight transport. However, under the Republic of China, the new-style bank discovered a benign opportunity to develop documentary railway billing service and created a bottom-up institutional reform model. Through the service, the bank became the new agent for the supervision of the transshipment company, which not only regulated the operation, but also forced railroad bureaus in the Yangzi Delta to be primarily responsible for railway freight. The Central Ministry of Transportation of Beiyang Government decided to promote this agency governance model and billing service nationwide.Received 11th January 2021; Revised 2nd June 2021; Accepted 20th July 2021